Rigid waist shift: A new method for local coupling corrections in the LHC interaction regions - Felix Soubelet; Tobias Persson; Rogelio Tomás; Oznur Apsimon; Carsten P. Welsch (Physical Review Accelerators and Beams, 2023)
Successful operation of large-scale particle accelerators depends on the precise correction of magnet field or alignment errors present in the machine. In the Large Hadron Collider (LHC), transverse linear coupling has been shown to have a significant impact on the beam dynamics. However, current measurement methods are not sufficient for precise local coupling measurement at the interaction point. In this paper, an approach to determine interaction region local coupling corrections with a rigid waist shift based on correlated global variables such as the closest tune approach |C^{-}| is presented. The validity of the method is demonstrated through simulations and experimental measurements taken during the LHC Run 3 commissioning in 2022, where determined corrections were applied and led to a measured luminosity increase of 9.7% and 3.5% at the ATLAS and CMS detectors, respectively.